Detrimental Effects of Leptin on Intracerebral Hemorrhage via the STAT3 Signal Pathway. Issue 6 (June 2013) - Kim, Chi Kyung; Ryu, Wi-Sun; Choi, In-Young; Kim, Young-Ju; Rim, Doeun; Kim, Beom Joon; Jang, Hyunduk; Yoon, Byung-Woo; Lee, Seung-Hoon
Leptin, one of the most important adipokines, is not only an energy regulator but also a regulator of innate immunity. Inflammation plays a key role in the tissue damage after intracerebral hemorrhage (ICH), and we sought to investigate whether leptin has a detrimental effect on ICH. After the injection of a high replacement dose (0.04 mg/kg) and two pharmacologic doses (4 and 8 mg/kg) of leptin, brain water contents increased significantly compared with that of control mice ( P < 0.05), which was confirmed when comparing the results with leptin-deficient ob/ob and wild-type (WT) mice (78.8% ± 0.6% versus 79.7% ± 0.6%, P < 0.05). The number of Ox6-positive microglia/macrophages was increased in the leptin-injected group and decreased in ob/ob compared with WT mice. Among the candidate signal transducers, an increase in signal transduction and activator of transcription 3 (STAT3) levels was found after leptin injection. When we administered NSC74859, a specific inhibitor of phosphorylated STAT3 (pSTAT3), the water content became normalized. Activity of pSTAT3 was found mainly in Ox6-positive microglia/macrophages, but not in either neurons or astrocytes. We demonstrate that leptin plays a critical role in the secondary brain injury around a hematoma and is a novel mediator of the inflammation. This detrimental effect of leptin on ICH is mediated by the STAT3 signaling pathway in inflammatory cells.